Freestyle - Galligan, Gale (New York, NY : Graphix, 2022)
While preparing for the last major dance competition before they graduate from eighth grade and go to separate high schools in NYC, Cory must balance the expectations of his parents, school, crew and his new friend as pressure mounts from all sides.
School Library Journal starred, October 2022
Pub Weekly, August 2022
Kirkus Starred, August 2022
3.6
5-8
GN320L
Keywords: Dance -- Competitions -- Comic books, strips, etc; Dance -- Competitions -- Juvenile fiction; Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Middle schools -- Comic books, strips, etc; Middle schools -- Juvenile fiction; New York (N.Y.) -- Comic books, strips, etc; New York (N.Y.) -- Juvenile fiction; Dance -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction; New York (N.Y.) -- Fiction; School comics; Graphic novels; Comics (Graphic works)